Design, Construction, and Validation of Histone-Binding Effectors in vitro and in Cells - Tekel, Stefan J. (Biochemistry, 2018)
Chromatin is a system of nuclear proteins and nucleic acids that plays a pivotal role in gene expression and cell behavior and is therefore the subject of intense study for cell development and cancer research. Biochemistry, crystallography, and reverse genetics have elucidated the macromolecular interactions that drive chromatin regulation. One of the central mechanisms is the recognition of post-translational modifications (PTMs) on histone proteins by a family of nuclear proteins known as “readers”. This knowledge has launched a wave of activity around the rational design of proteins that interact with histone PTMs. Useful molecular tools have emerged from this work, enabling researchers to probe and manipulate chromatin states in live cells. Chromatin-based proteins represent a vast design space that remains underexplored. Therefore, we have developed a rapid prototyping platform to identify engineered fusion proteins that bind histone PTMs in vitro and regulate genes near the same histone PTMs in living cells. We have used our system to build gene activators with strong avidity for the gene silencing-associated histone PTM H3K27me3. Here, we describe procedures and data for cell-free production of fluorescently tagged fusion proteins, enzyme-linked immunosorbent assay-based measurement of histone PTM binding, and a live cell assay to demonstrate that the fusion proteins modulate transcriptional activation at a site that carries the target histone PTM. This pipeline will be useful for synthetic biologists who are interested in designing novel histone PTM-binding actuators and probes.